VARIOUS CONJUNCTIONS IN THE BOOK OF FLOATING IN SPACE BY NAELA ALI USING HALLIDAY AND HASAN THEORY - Wanda Anastania; Chintia Handayani (Asosiasi Dosen Muda Indonesia, 2023)
In this study, we analyzed the various conjunctions that appear in Naera Ali's book Floating in Space. The purpose of the study is to find out the various of conjunctions and which ones are used most often in each conversation in the book. This study used qualitative methods. This study is based on the theory of Halliday and Hasan (1976). Types of conjunctions include additive, inverse, causal, and temporal. The researchers found that there were 192 conjunctions data for every conversation. The details are: 100 additive data, 41 adversarial data, 48 causal data, and 3 temporal data. The most commonly used conjunction is addition.